If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60x + 11y = 30 Solving 60x + 11y = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. 60x + 11y + -11y = 30 + -11y Combine like terms: 11y + -11y = 0 60x + 0 = 30 + -11y 60x = 30 + -11y Divide each side by '60'. x = 0.5 + -0.1833333333y Simplifying x = 0.5 + -0.1833333333y
| 3+6x=13+16x | | 6y-4=5-8y | | 6*x-17=7 | | 4t+b=q | | 6*x-10=7 | | -7(-9x-29)=1274 | | 36=x(12-3) | | 6y-20y= | | 9(m+2)=9m+18 | | 4r^2+11r+6=0 | | -5x+4=-40 | | 1.07/x=15/100 | | D=x(f-d) | | f(x)=cos^5x | | tanx=0.2 | | 5-[-2]= | | x^4-6x^3-9x^2-54x-162=0 | | 5(x-8)=-42+5x | | 3y^2+3y+6=0 | | 2(n-8)-n=n-16 | | 7b^2+29b-30=0 | | -112=-27-5x | | -4(6a-2)= | | 90(x+24)+90(x)=4x(x+4) | | 14.5y=6 | | 21nx-3=0 | | 7a+2=5a+3 | | 7x-10=3(x-2)+5(x-1) | | 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= |